A Numerical Investigation to Enhance Latent Heat Thermal Energy Storage Through the Utilization of Spiral Fins Composed of Aluminum - Abdulaaima, karrar A.; Al-Hattab, Tahseen A. (Journal of Petroleum Research and Studies, 2025)
The use of phase change materials (PCM) to store latent thermal energy is critical to bridging the disparity between energy production and consumption. This paper investigates numerically the use of double and quadruple spiral fins, spiral foam fins, and rectangular and cylindrical fins in the horizontal position to improve heat transfer in a shell-and-tube heat exchanger and compares the different types with the finless design. Comsol Multiphysics (6.0) was used to create a 3D model. In this simulation, natural convection was taken into account, and an approximately equal amount of phase change material was used in all cases. Water as the heat transfer fluid and commercial paraffin (RT-28) as the phase change material were used in this simulation. The results show that the melting time was significantly decreased when the spiral fins were used, and the heat transfer rate was significantly improved when the spiral foam fins were used.